Mediasi Keagamaan MUI dalam Fatwa Nomor 24 Tahun 2017 dan Analisis Maqāṣid Al-Syarī‘Ah di Era Digital: Religious Mediation by the Indonesian Council of Ulama (MUI) in Fatwa No. 24 of 2017 and the Analysis of Maqāṣid Al-Sharī‘Ah in the Digital Era - Syarif, Muh Isra; Kurniati; Misbahuddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
The development of digital technology has created a new sphere for social interaction and Islamic da‘wah while simultaneously opening opportunities for conflicts arising from the spread of hoaxes, slander, and hate speech based on religion. In this context, the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) plays an important role as a religious institution that not only issues legal fatwas but also performs a function of social mediation. This study aims to analyze MUI’s mechanism of religious mediation through Fatwa No. 24 of 2017 on the Law and Guidelines for Social Interaction via Social Media, by examining the extent to which maqāṣid al-sharī‘ah (the higher objectives of Islamic law) are reflected in its substance and objectives. This research employs a qualitative-descriptive approach combined with a normative-sociological perspective and is categorized as library research. The primary data are derived from the official text of the MUI fatwa, while secondary data include the Qur’an, hadith, classical uṣūl al-fikih works, and relevant academic literature. The analysis uses content analysis guided by the framework of maqāṣid al-sharī‘ah. The findings reveal that MUI Fatwa No. 24/2017 embodies the values of protecting religion (ḥifẓ al-dīn), intellect (ḥifẓ al-‘aql), and honor (ḥifẓ al-nasl), and functions as a form of normative mediation in maintaining ethical digital communication. The contribution of this study lies in strengthening the discourse of fikih al-islāḥ (the jurisprudence of reconciliation) within contemporary Islamic law, by offering a maqāṣid-based perspective in understanding fatwas as social instruments for fostering peace in the digital era.